Purwarupa Sistem Pemilihan Umum Elektronik dengan Pemanfaatan Protokol Ethereum pada Teknologi Blockchain - Arianto, Eko; Umam, Chaerul; Handoko, L Budi (Jurusan Teknologi Informasi Universitas Semarang, 2021)
The development of information technology has penetrated various areas. This is driven by improved service, rapid increase in information needs and decision making. General elections that are held every time always leave problems about securities and speed of recapitulation. This is because the process is done in the traditional way. This research tries to apply blockchain technology to the e-Voting system security engineering process so that it creates a votes recapitulation process that is fast, accurate and accompanied by transparency values to maintain the reliability of the existing vote and maintain the confidentiality of the vote data being transacted. Transparency and confidentiality of voter data is a fundamental value in general elections or voting that must exist. Seeing this, blockchain technology deserves to be applied because the principles that needed can be met by applying this technology to the e-Voting system.